A retrospective comparative study on stapler verses hand sewn technique in gastrointestinal anastomosis of twenty-five cases each - Mehta, Anuj; Sharma, Praveen; Pancholi, Mukesh; Patel, Parth (International Surgery Journal, 2023)
Background: In gastrointestinal surgery after resection of bowel loops, anastomosis of the bowel loops forms the main part of the surgery. The evolution of mechanical sutures by stapler devices is a technological advancement which helps anastomosis of bowel loops with less tissue injury and decreased time duration of procedure. Objective of current study was to compare the hand sewn anastomosis with stapler anastomosis in various types of elective gastrointestinal surgeries. Methods: A retrospective comparative study was conducted in department of general surgery at New Civil Hospital, Surat. The study included 50 patients of either gender and different age groups. Results: Out of 50 patients, 7 patients had Benign Gastric Outlet Obstruction (GOO), 18 patients had Post corrosive esophageal stricture, 5 patients had obstruction, 6 patients had post ileostomy status, 5 patients had carcinoma of ascending colon, 1 patient had carcinoma of caecum, 4 patients had ileo-caecal growth, 3 patients had carcinoma of descending colon, and 1 patient had sigmoid colon growth. In stapler anastomosis group Mean Total operative time was (156.20±45.21) mins whereas in handsewn anastomosis group Mean Total operative time was (188.40±48.32) mins with p value of 0.019. Conclusions: In this study, one distinct advantage of staplers was the consistent reduction in operating time. However, no significant difference was found between the stapler and hand-sewn groups with respect to other parameters such as restoration of intestinal function, postoperative hospital stay, and postoperative complications like leakage, fistula or stricture formation.